ANALISIS PERUBAHAN HARGA SAHAM BANK SYARIAH BUMN SEBELUM MERGER DAN PASCA MERGER - Hendrik Suhendri; Sri Indah; Abdul Haris Al-Abi Syahril (Unitri Press, 2022)
Purpose: This study aims to determine the closing stock prices of state-owned Islamic banks before and after the merger. The government hopes that this merger between state-owned Islamic banks will be able to strengthen the capital structure of the national economy, Methods: This type of research is quantitative. The closing share prices of state-owned Islamic banks before and after the merger are documented, Analysis data: The results of the Kolmogorov-Smirnov data normality test show that the value of each closing price before and after the merger is 0.00 and 0.00 (less than 0.05). Because the data is not normally distributed (less than 0.05), the analysis tool used is the Wilcoxon signed rank test, Result and discussions: The result of the Wilcoxon signed rank test is 0.00 (less than 0.05). This can be interpreted that there is a difference in the closing price of the shares after the merger which is higher than the closing price of the shares before the merger, Conclusion: The closing price of shares after the merger is higher than the closing price of shares before the merger. This indicates the importance of strengthening the capital structure in the midst of unstable national economic conditions, especially during the Covid-19 pandemic. Future research can include the dividend variable to determine the impact of the merger from the shareholder side.Tujuan: Penelitian ini bertujuan untuk mengetahui harga saham penutupan bank syariah BUMN sebelum merger dan pasca merger. Pemerintah berharap merger antar bank Syariah BUMN ini mampu memperkuat struktur permodalan perbankan syariah nasional., Metode: Jenis penelitian ini adalah kuantitatif. Harga saham penutupan bank-bank syariah BUMN sebelum merger dan sesudah merger didokumentasikan, Analisis data: Hasil uji normalitas data Kolmogorov-Smirnov menunjukkan nilai masing-masing data harga saham penutupan sebelum dan pasca merger adalah 0,00 dan 0,00 (nilainya kurang dari 0,05). Oleh karena datanya tidak terdistribusi normal (kurang dari 0,05), maka alat analisis yang digunakan adalah Wilcoxon signed rank test, Hasil dan diskusi: Hasil uji Wilcoxon signed rank nilainya adalah 0,00 (kurang dari 0,05). Ini bisa dimaknai bahwa ada perbedaan harga saham penutupan pasca merger yang lebih tinggi dibandingkan harga saham penutupan sebelum merger. Kesimpulan: Tingginya nilai harga saham penutupan pasca merger dibandingkan dengan harga saham penutupan sebelum merger. Ini mengindikasikan pentingnya penguatan struktur permodalan di masa perekonomian yang tidak stabil, khususnya di masa pandemic Covid-19. Penelitian lebih lanjut bisa memasukkan variabel deviden untuk mengetahui dampak merger dari sisi shareholder.